DAYA ANTIBAKTERI BERBAGAI KONSENTRASI MINYAK ATSIRI RIMPANG TEMU HITAM (Curcuma aeruginosa roxb.) TERHADAP Bacillus subtilis DAN Staphylooccus aureus SECARA IN VITRO - Khodijah Baharun; MG. Isworo Rukmi; Arina Tri Lunggani; Enny Fachriyah (Departemen Biologi, Fakultas Sains dan Matematika Undip, 2013)
The rhizome of Curcuma aeruginosa has essential oils compounds and has been used traditionally to help for nourish the skin, asthma, appetite enhancer, and as anthelmintik. Bacillus subtilis and Staphylococcus aureus are gram positive bacteria that can cause skin disorder such allergic and acne. The aim of this research was to know antibacterial capacity of essential oils from C. aeruginosa in various concentrations against B.subtilis and S.aureus using disc diffusion method. This research was conducted using RAL design (Completely Randomized Design) with concentration of essential oils as a treatment, i.e. 25, 50, 75, and 100% (pure extract without dilution). The result showed that essential oils of C. aeruginosa has antibacterial capacity for both bacteria with different effect depending on the concentrations tested. Essential oils of C. aeruginosa with 100% concentration showed the highest antibacterial capacity against S. aureus, whereas all concentrations of essential oils from C. aeruginosa showed weak antibacterial capacity against B. subtilis. Keyword : Curcuma aeruginosa Roxb., distillation, essential oils, antibacterial, S.aureus, B.subtilis